Конституційні засади захисту прав і свобод дитини в Україні: досвід, проблеми, перспективи - Кудрявцева, О.; Kudryavtseva, О. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
Стаття присвячена актуальним питанням теорії та практики утвердження та функціонування конституційних засад захисту прав і свобод дитини в Україні. Аналізуються витоки і досвід забезпечення прав і свобод дитини у міжнародних документах і національних конституціях, а також відповідна правозастосовна практика. Визначаються проблеми забезпечення прав дітей в умовах проведення антитерористичної операції (АТО) на Сході України. Досліджуються перспективи удосконалення конституційних засад захисту прав і свобод дитини в Україні та обґрунтовуються пропозиції щодо вдосконалення Конституції України, а також цивільного та сімейного законодавства. The article is devoted to the vital theoretical and practical issues of establishment and functioning of the constitutional basis for the protection of rights and freedoms of the child in Ukraine. The origins and experience in ensuring the rights and freedoms of the child in international documents, in particular the Convention on the Rights of the Child of 1989, national constitutions and laws, and appropriate legal practice, are analyzed. Problem of ensuring the rights of the child during counterterrorism operation (CTO) in the Eastern part of Ukraine are stated. In particular, problem of the children who remain in the war zone in the cities of Donetsk and Lugansk regions, as well as of the children-migrants, is uncovered. The author researched the prospects of improving constitutional principles for protecting the rights and freedoms of children in Ukraine and grounded proposals to improve the Constitution of Ukraine, civil and family law.
The Constitutional Bases of Child’s Rights and Freedoms Protection in Ukraine: Experience, Problems and Prospects
Keywords: дитина; правовий статус дитини; конституційна правосуб’єктність дитини; захист прав і свобод дитини; child; rights and freedoms of the child; the constitutional legal capacity of the child; protection of the rights and freedoms of the child